2007
DOI: 10.1016/j.neuroimage.2006.08.045
|View full text |Cite
|
Sign up to set email alerts
|

The effect of large veins on spatial localization with GE BOLD at 3 T: Displacement, not blurring

Abstract: We used two different methods of region of interest (ROI) definition to investigate the spatial accuracy of functional magnetic resonance imaging (fMRI) at low and high spatial resolution. The "singlecondition localizer" consisted of block alternation between a target stimulus and a mean gray background. The "differential localizer" consisted of block alternation between the target stimulus and another stimulus that filled the complement of the visual field. A separate series of scans, in which the target stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
88
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(93 citation statements)
references
References 31 publications
5
88
0
Order By: Relevance
“…Since the hemodynamic response is typically thought to be the dominant factor, it is likely that the inversion originates from a hemodynamic effect rather than metabolic change. Inverted HRFs similar to those reported here have also been reported by Olman et al who showed rather convincingly that they were of vascular origin (Olman et al, 2007). As with the inverted responses analyzed here, those reported by Olman et al were found intermixed with positive HRFs within the cortical representation of the stimulus.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Since the hemodynamic response is typically thought to be the dominant factor, it is likely that the inversion originates from a hemodynamic effect rather than metabolic change. Inverted HRFs similar to those reported here have also been reported by Olman et al who showed rather convincingly that they were of vascular origin (Olman et al, 2007). As with the inverted responses analyzed here, those reported by Olman et al were found intermixed with positive HRFs within the cortical representation of the stimulus.…”
Section: Discussionsupporting
confidence: 92%
“…In such cases, modeling the HRF completely for each voxel may be necessary. Despite these limitations, correcting for inverted HRFs improves the uniformity of cortical maps and suggests that a detailed accounting of HRF properties can recover fMRI information that might otherwise be discarded as artifactual (Olman et al 2007; Winawer et al 2010). It also suggests that if the inversion reflects a blood steal effect then the region “stealing” the blood must be nearly adjacent to the inverted HRF voxel as this correction method would fail to improve the retinotopic maps if the stealing region encoded a different retinotopic location.…”
Section: Discussionmentioning
confidence: 99%
“…Areas of low mean fMRI signal, corresponding to pial draining veins (Olman et al, 2007;Winawer et al, 2010), were excluded from subsequent analysis (except for the computation of the V1 surface area).…”
Section: Methodsmentioning
confidence: 99%
“…Further selection criteria were applied based on mean-normalized variance: for the primary analysis, voxels were sorted by mean-normalized variance (i.e., variance in ER scans after signal was converted to percent signal change) and the top 20% were discarded from the ROI in order to minimize the contribution of large pial vessels to the signal (de Zwart et al, 2005; Olman et al, 2007). Removing this constraint to include all voxels produced qualitatively similar patterns of results with slightly decreased significance for the long ISI data, but increased significance for the short ISI data.…”
Section: Methodsmentioning
confidence: 99%